Towards the humane slaughter of decapod crustaceans: identifying the most effective indicators of insensibility following electrical stunning - Neil, Douglas M.; Putyora, Endre; Albalat, Amaya (Frontiers in Animal Science, 2024)
Decapod crustaceans provide a valuable food source worldwide, both through wild capture and captive rearing. They are also used extensively in scientific research, both as subjects for the investigation of basic biological processes and as model organisms for the detection of environmental changes. There is now an increasing acceptance that decapod crustaceans are sentient, and legislation is being introduced in numerous countries to ensure crustacean welfare when they are harvested or held captive. Moreover, methods for the humane slaughter of these animals are being developed, and of these electrical stunning is a prime candidate. Optimisation of electrical stunning is underway for a range of commercially-exploited or scientifically-important species, and the present study contributes to that process by examining further crab (Carcinus maenas) and lobster (Homarus gammarus) species using a rigorous neurophysiological approach. By recording nerve activity in both the central and peripheral nervous systems, we have found that electrical stunning with a standard commercial instrument arrests nerve activity in both these species at all levels: sensory, motor and central, rendering the animals neurologically insensible. This methodology is the most direct and effective way to establish if insensibility is successfully achieved. However, ultimately the routine monitoring of effective stunning in commercial and laboratory settings will have to depend on simple, yet reliable physiological or behavioural indicators, following their calibration against neurological methods. Monitoring heartbeat is used widely to establish metabolic activity, locomotory performance, agonistic interactions and responses to environmental conditions. We have therefore assessed the potential to use cardiac activity as an indicator for the state of sensibility. We recorded the heartbeat in both C. maenas and H. gammarus before and after electrical stunning, but find that in many cases even though nerve activity has ceased both centrally and peripherally, cardiac activity actually continues (though at a reduced rate) for a substantial time (>1h). The heartbeat is therefore not a reliable indicator of the state of sensibility, making it an unsuitable indicator of effective stunning. Possible reasons for these findings, and ways to validate behavioural measures that may be more appropriate for routinely establishing effective electrical stunning, are discussed.